Impact of Food Origin Lactiplantibacillus plantarum Strains on the Human Intestinal Microbiota in an in vitro System - Garcia-Gonzalez, Natalia; Comas, Joan Colom; Harris, Hugh M. B.; Strain, Conall; Stanton, Catherine; Hill, Colin; Corsetti, Aldo; Gahan, Cormac G. M. (Frontiers in Microbiology, 2022)
We have previously isolated and characterized food-dwelling strains of Lactiplantibacillus (Lpb.) plantarum that are consumed naturally as part of the microbiota of table olives and raw milk cheeses. Despite being consumed at relatively high levels, the impact of such strains on the human gut microbiota is currently unclear. In the current study we evaluated the potential impact of food-dominant Lpb. plantarum strains on the human gut microbiota using a continuous fecal fermentation system. Daily inoculation of Lpb. plantarum strains led to significant, detectable levels in the fecal fermentation system. We examined the impact of the presence of Lpb. plantarum on the microbiota derived from two separate donors. For one donor, Lpb. plantarum increased alpha diversity and beta diversity. This was reflected in significant alterations in abundance of the unclassified genera, dominated by Enterobacteriaceae_unclass and Ruminococcaceae_unclass. The microbiota of the other donor was relatively unaffected following introduction of the Lpb. plantarum strains. Overall, the work describes the response of the human microbiota to the introduction of high levels of food-dominant Lpb. plantarum strains and indicates that the response may reflect interindividual differences between donor samples.